2017
DOI: 10.1080/02670836.2017.1300365
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature mechanical properties of Inconel-625: Role of carbides and delta phase

Abstract: Based on the temperature sensitivity characteristics, high-temperature tensile tests were performed at different temperatures and after different solid solution treatments to investigate the effect of Cr-rich M23C6, Nb-rich MC and the delta phase on the mechanical properties of Inconel 625. The experimental results indicated that the Cr-rich M23C6 carbides and the Nb-rich MC carbides decomposed at 700°C, which could be the reason for resulting tensile strength anomaly that was observed in a narrow temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…It is worth noting that the continuous coarsening of the δ phase precipitates observed at 870 °C was not apparent at 700 °C, suggesting stability against significant coarsening at 700 °C, which is possibly due to the stabilization provided by the elastic energy of the strain field surrounded by the precipitates [ 49 ]. This limited growth of the δ phase precipitates during the long heat treatment at 700 °C is significant because the overgrown δ phase leads to reduced fracture strain [ 50 ]. Moreover, a recent review shows that direct aging at 700 °C for 24 h also leads to the highest reported UTS (1222 MPa) and yield strength (1012 MPa) for AM IN625, suggesting that the formation of smaller precipitates serves to improve the mechanical strength [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the continuous coarsening of the δ phase precipitates observed at 870 °C was not apparent at 700 °C, suggesting stability against significant coarsening at 700 °C, which is possibly due to the stabilization provided by the elastic energy of the strain field surrounded by the precipitates [ 49 ]. This limited growth of the δ phase precipitates during the long heat treatment at 700 °C is significant because the overgrown δ phase leads to reduced fracture strain [ 50 ]. Moreover, a recent review shows that direct aging at 700 °C for 24 h also leads to the highest reported UTS (1222 MPa) and yield strength (1012 MPa) for AM IN625, suggesting that the formation of smaller precipitates serves to improve the mechanical strength [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, at 760 °C, the elongations to failure decreased significantly, especially after ST. Thus, the two alloys manifested the so-called elevated temperature ductility loss ( ) observed in many Ni-based alloys [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. This ductility loss reached its maximum after the solution treatment, and despite the dissolution of the δ phase, chemical homogenization and microstructure coarsening resulted from the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Ni-based superalloy Inconel 625 (IN625) is a popular material for gas turbine applications characterized by good high temperature strength, creep resistance, corrosion resistance and excellent weldability [7][8][9][10]. Due to this excellent weldability, fabrication of IN625 by SLM is particularly appropriate and has been properly optimized [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%